Revitalization of the INA-CBG’S Application Interface at Wava Husada Hospital - Aprilia, Sendi Fantri; Afifah, Nur; Annastasia, Shinta; Gading, Rahmaninda Putri; Jamilah, Nuril Khabibatul; Yulianti, Puput Dwi; Dasilva, Elisabet Natali Sonya; Rusdi, Ahmad Jaelani; Ma'ruf, Agus Syukron; Duana, Farma (AMK : Abdi Masyarakat UIKA, 2025)
The completeness of diagnosis is something that medical recorders must pay attention to. The completeness of diagnosis is very important in the fields of clinical data management, cost reimbursement, and health care and services. INA-CBG's (Indonesia Case Groups) is an application used by all hospitals, one of which is Wava Husada Kepanjen Hospital, in submitting claims using a package system based on the illness suffered. The method of implementing this activity involves explaining the necessary updates to the diagnosis coding system, which will be automatically bridged to the INA-CBGs application. The activity was conducted at Wava Husada Hospital, specifically in the CASE MIX unit. The method of implementing this activity was to explain the parts that needed to be updated or corrected, conduct hands-on practice with each user, and hold a question and answer session regarding obstacles in its use. The socialization activity proceeded smoothly, and staff members felt assisted by the changes made to the system, which had been adapted to user needs. However, during implementation, staff members still need to perform double checks to anticipate errors related to the assignment of diagnosis codes. This is because the system lacks prompts to remind staff members about the completeness or accuracy of diagnosis code entry, resulting in frequent errors made by CASE MIX staff members.